Successful obliteration of troublesome and chronically draining cavities. Issue 2 (10th January 2017) - Geerse, S; Ebbens, F A; de Wolf, M J F; van Spronsen, E
Abstract: Objective: This study aimed to evaluate the results of revision radical cavity surgery with mastoid obliteration using a standardised grading scheme. Methods: A retrospective study was performed of 121 patients (122 ears) with chronically draining ears who underwent revision radical cavity surgery with mastoid obliteration between 2007 and 2013. Surgical indications, patient characteristics, pre- and post-operative Merchant grade, and surgical outcomes were recorded. The main outcome measures were presence of a dry ear, time for complete re-epithelialisation, presence of residual or recurrent disease, and need for revision surgery. Results: In the 5-year follow-up group ( n = 31), dry ears were found in 97 per cent after 6 minor revisions and cholesteatoma-free ears were found in 97 per cent. In the total cohort, dry ears were found in 93 per cent after nine revisions and cholesteatoma-free ears were found in 98 per cent. The median time for complete re-epithelialisation was eight weeks. There were no major complications. Conclusion: In terms of the dry ear rate, residual cholesteatoma and time to complete epithelialisation, revision radical cavity surgery with mastoid obliteration produces very good results in concordance with published results, despite most patients suffering from very troublesome cavities prior to surgery.